Perilaku Keluarga dalam Mencari Pertolongan Kesehatan Bagi Anggota Keluarganya yang Mengalami Gangguan Jiwa - I Wayan Candra (Jurnal Gema Keperawatan, 2013)
Behavior in health seeking families for family members who experience mental illness. This study aims to determine the behavior of the family in seeking medical help for family members who are sick in soul polyclinic Sanglah Denpasar. This research is descriptive research, the approach to the subject with a cross sectional study. Using purposive sampling techniques sampling with a sample of 30 respondents. The results of 30 people found the majority of respondents 19 (63,3%) families looking for fist aid for family members who are mentally handicapped go to atraditional healer/shaman, the bulk of 23 people (76,7%) continued to seek help families with to sick help before the healer/shaman, shackle, and confining, and most of 22 people (73.3%) care for family members who experience mental illness at home as directed healer/shaman, shackle, and imprison her home.